Penyuluhan Kesehatan Mengenai Pengetahuan Tentang Diabetes Mellitus Dan Kegiatan Senam Diabetes Mellitus Pada Lansia Di Dusun II Desa Pekik Nyaring, Bengkulu Tengah - Muqaromah, Asmi; Permatasari, Ayu; Zubiyo, Ahmad; Lestari A, Sela Nova; Susanti, Meri Epriana; Annisa, Kintan (LPPM Universitas Dehasen Bengkulu, 2024)
Diabetes Mellitus (DM) is a disease that has been increasingly found lately. Diabetes Mellitus is also often referred to as diabetes or blood sugar disease. This one disease is a type of chronic disease whose initial sign is an increase in blood sugar levels as a result of a metabolic system disorder in the body. The organ that is disturbed is the pancreas which is no longer functioning as it should. The pancreas is no longer able to produce the hormone insulin in meeting the needs of the body. One of the factors that affect diabetes mellitus is a lack of knowledge. Public knowledge about diabetes mellitus is needed as a foundation for society in showing diabetes mellitus prevention behavior. Knowledge is very important for the formation of a behavior (Donsu, 2017). Knowledge is also related to the level of education. The higher a person's education level, of course, the more information they will have, which will affect a person's behavior (Notoatmodjo, 2002). One alternative in dealing with diabetes mellitus is to do diabetes mellitus exercises. Objective : At the end of the counseling process, all the elderly and pre-elderly in Hamlet II of Pekik Nyaring Village can understand and understand about Diabetes Mellitus and participate in doing diabetes mellitus exercises. Methods : The methods used in counseling about diabetes mellitus are lectures and questions and answers and distributing leaflets. Then the diabetes mellitus gymnastics method used is by direct practice of diabetes mellitus gymnastics. Results and Discussion : In this counseling activity, the elderly experienced an increase in knowledge from the pre-test with an average of 65 and the post-test with an average of 80, with a difference of 15. The final result of this diabetes mellitus gymnastics activity made the cadres agree to do diabetes mellitus gymnastics for the elderly at least 1-2 times every month.